Resin composition
By using resin compositions such as bismaleimide resin, the problem of high dielectric loss in high frequency communications of traditional epoxy resin is solved, and the low dielectric constant and low dielectric required for high frequency printed circuit boards are achieved Electrical loss improves the heat resistance and electrical properties of the material.
Patent Information
- Application Number
- CN202311228585.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-23
- Filing Date
- 2023-09-22
- Publication Date
- 2025-02-25
AI Technical Summary
Traditional epoxy resins have high dielectric loss in high-frequency communication applications and cannot meet the rapidly developing high-frequency communication needs.
A resin composition mainly consisting of bismaleimide resin is used to form a substrate material with excellent electrical properties in combination with epoxy resin, benzooxazine resin, hardener, filler and coupling agent.
It achieves high glass transfer temperature, low dielectric constant and low dielectric loss, and is suitable for high-frequency printed circuit boards, improving the heat resistance and electrical properties of the material.
Smart Images

Figure BDA0004463118060000031 
Figure BDA0004463118060000041 
Figure BDA0004463118060000091
Abstract
Description
Technical Field
[0001] The present invention relates to a composition, and in particular to a resin composition. Background Art
[0002] In recent years, due to the development of 5G communication and millimeter wave communication, mobile phones, base stations, servers, etc. are applied to higher frequencies (6~77GHz), so higher frequency substrate materials must be used to be suitable for 5G high frequency. The dielectric constant of traditional epoxy resin (Epoxyresin) is approximately between 3.5 and 5.0, and the dielectric loss is greater than 0.01, which is high in dielectric loss. It is no longer sufficient for the rapidly developing high-frequency communication applications. In addition, the direct application of amine hardeners and phenolic resin hardeners to copper foil substrates cannot overcome the disadvantage of excessively high transmission loss. Therefore, it is still necessary to develop materials with excellent electrical properties and meet the characteristics of high-frequency printed circuit boards, such as materials with high glass transition temperature, low dielectric constant and low dielectric loss. Summary of the invention
[0003] The present invention provides a resin composition, comprising: based on the total weight of the resin composition, 30 wt % to 50 wt % of a bismaleimide resin; 1 wt % to 10 wt % of an epoxy resin; 1 wt % to 10 wt % of a benzoxazine resin; 1 wt % to 5 wt % of a hardener; 10 wt % to 40 wt % of a filler; and 0.1 wt % to 3 wt % of a coupling agent.
[0004] In one embodiment of the present invention, the bismaleimide resin includes DCPD-BMI, KI-50P, KI-70, MIR-3000, MIR-5000 or a combination thereof.
[0005] In one embodiment of the present invention, the weight percentage of the epoxy resin is 1 weight % to 3 weight %.
[0006] In one embodiment of the present invention, the resin composition further comprises 0.1 wt % to 3 wt % of a catalyst.
[0007] In one embodiment of the present invention, the resin composition further comprises 5 wt % to 15 wt % of a flame retardant.
[0008] The present invention provides an electronic component, comprising a substrate formed from the above resin composition.
[0009] In one embodiment of the present invention, the substrate has a dielectric constant less than or equal to 3.5 at a frequency of about 10 GHz.
[0010] In one embodiment of the present invention, the substrate has a dielectric loss less than or equal to 0.003 at a frequency of about 10 GHz.
[0011] In one embodiment of the present invention, the glass transition temperature of the substrate is greater than or equal to 260°C.
[0012] In one embodiment of the present invention, the substrate is a copper foil substrate.
[0013] Based on the above, the resin composition of the present invention has the characteristic of not generating polar groups during the reaction, so it is not easily polarized in the electric field, thereby being able to significantly reduce its dielectric constant. In addition, the resin composition of the present invention can achieve a high glass transition temperature (greater than or equal to 260°C), a low dielectric constant (less than or equal to 3.5) and a low dielectric loss (less than or equal to 0.003) in the application of copper foil substrates. DETAILED DESCRIPTION
[0014] The following are examples of the present invention. The implementation details provided in the examples are for illustration purposes only and are not intended to limit the scope of the present invention. Anyone with ordinary knowledge in the art can modify or change these implementation details according to the needs of the actual implementation.
[0015] Ranges may be expressed herein as from "about" one particular value to "about" another particular value, which may also be expressed directly as one particular value and / or to another particular value. When expressing the range, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when a value is expressed as an approximation by using the antecedent "about," it will be understood that the particular value forms another embodiment. It will be further understood that the endpoints of each range may be expressly related to or independent of the other endpoint.
[0016] In this document, non-limiting terms (such as may, could, for example, or other similar terms) mean optional or optional implementation, inclusion, addition, or presence.
[0017] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs. It will also be understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the relevant technical context and should not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.
[0018] Herein, the so-called “divalent organic group” is an organic group having two bonding positions, and the “divalent organic group” can form two chemical bonds through the two bonding positions.
[0019] The present invention provides a resin composition, comprising: based on the total weight of the resin composition, 30 to 50 weight percent of bismaleimide (BMI) resin; 1 to 10 weight percent of epoxy resin; 1 to 10 weight percent of benzoxazine resin; 1 to 5 weight percent of hardener; 10 to 40 weight percent of filler; and 0.1 to 3 weight percent of coupling agent. The present invention uses bismaleimide resin in combination with epoxy resin, benzoxazine resin, hardener, filler and coupling agent to improve the heat resistance of high-frequency substrate materials and reduce the dielectric constant and dielectric loss of high-frequency substrate materials.
[0020] In some embodiments, based on the total weight of the resin composition, the weight percentage of the bismaleimide resin is 30 wt % to 50 wt %, such as 35 wt %, 40 wt % or 45 wt %.
[0021] In some embodiments, the bismaleimide resin has a structure represented by the following formula (1):
[0022]
[0023] Wherein, L represents a dicyclopentadienyl group, a divalent organic group derived from a phenolic compound, or a combination thereof,
[0024] L 1 and L 2 each represents a divalent organic group derived from a phenolic compound, and
[0025] m represents an integer from 0 to 18. In some embodiments, the above-mentioned phenolic compound includes phenol. In some embodiments, the above-mentioned divalent organic group is preferably a divalent organic group including a maleimide group. In some embodiments, L is preferably a combination of a dicyclopentadienyl group and a divalent organic group derived from a phenolic compound. In some embodiments, L represents
[0026] or a combination thereof, wherein * represents a bonding position. In some embodiments, L 1 and L 2 Each expressed Where * indicates the bonding position.
[0027] In some embodiments, the bismaleimide resin has a structure represented by the following formula (2):
[0028]
[0029] Wherein, m represents an integer of 0 to 18, preferably 2 to 10.
[0030] For example, the synthesis method of bismaleimide resin includes the following steps. First, 1 mol of dicyclopentadiene phenolic resin (trade name ERM6140, manufactured by Songyuan Company, weight average molecular weight 1,300) and 1.25 mol of 4-halonitrobenzene (wherein the halogen can be fluorine, chlorine, bromine or iodine) are added to 6 mol of dimethylacetamide (DMAC) as a reaction solvent, and reacted at a temperature of 120° C. for 300 minutes to perform a nitration reaction. Then, hydrogen is introduced and reacted at a temperature of 90° C. for 480 minutes to perform a hydrogenation reaction to form a modified dicyclopentadiene type diamine. Next, 3 mol of maleic anhydride and 9.7 wt % of toluenesulfonic acid were added, and the mixture was reacted at 120° C. for 420 minutes to obtain a second resin, which is a bismaleimide resin (DCPD-BMI) having a dicyclopentadiene structure as the main chain, having a structure represented by formula (2), and an average molecular weight of 800 to 10,000, preferably 1,000 to 4,000.
[0031] In some embodiments, the weight percentage of the epoxy resin is 1 wt % to 10 wt %, such as 2 wt %, 4 wt % or 6 wt %, based on the total weight of the resin composition. In some embodiments, the epoxy resin is an epoxy resin with a trade name of 437 provided by NANYA Plastics Industry Co., Ltd.
[0032] In some embodiments, the weight percentage of the benzoxazine resin is 1 wt % to 10 wt %, such as 2 wt %, 4 wt % or 6 wt %, based on the total weight of the resin composition. In some embodiments, the benzoxazine resin is a benzoxazine resin with a trade name of 234 provided by NANYA Plastics Co., Ltd.
[0033] In some embodiments, the weight percentage of the hardener is 1 wt % to 5 wt %, such as 2 wt %, 3 wt % or 4 wt %, based on the total weight of the resin composition. In some embodiments, the hardener is a hardener provided by DIC (Dainippon Ink & Chemicals, Inc.) under the trade name HPC-8000.
[0034] In some embodiments, the weight percentage of the filler is 10 wt % to 40 wt %, such as 20 wt %, 25 wt % or 30 wt %, based on the total weight of the resin composition. In some embodiments, the filler has a spherical shape, and the particle size (D50) of the filler is 0.3 μm to 3 μm. In some embodiments, the maximum particle size (D99) of the filler is not greater than 10 μm. In some embodiments, the filler contains a surface modification of acrylic or vinyl. In some embodiments, the filler is a silicon dioxide (SiO2) filler provided by SIBELCO.
[0035] In some embodiments, the weight percentage of the coupling agent is 0.1 wt % to 3 wt %, such as 0.5 wt %, 1 wt % or 1.5 wt %, based on the total weight of the resin composition. Adding a coupling agent can enhance the compatibility and crosslinking degree of the resin composition with glass fiber cloth and powder. In some embodiments, the coupling agent content in the resin composition is 0.1 parts per hundred parts of resin (phr) to 5phr of coupling agent per hundred parts of resin. In some embodiments, the coupling agent content in the resin composition is 0.5phr to 1phr. In some embodiments, the coupling agent is a siloxane coupling agent. In some embodiments, the coupling agent is vinyl silane or acrylic silane. In some embodiments, the coupling agent is a coupling agent provided by Dow Chemical (DOW) under the trade name Z-6030.
[0036] In some embodiments, the resin composition further comprises a flame retardant. In some embodiments, the weight percentage of the flame retardant is 5 wt % to 15 wt %, such as 8 wt %, 10 wt % or 12 wt %, based on the total weight of the resin composition. In some embodiments, the flame retardant is a phosphorus-based flame retardant. In some embodiments, the flame retardant is a flame retardant with a trade name of PX200 provided by Daba Chemical Company.
[0037] In some embodiments, the resin combination further comprises a catalyst. In some embodiments, the weight percentage of the catalyst is 0.1 wt % to 3 wt %, such as 0.5 wt %, 1 wt % or 1.5 wt %, based on the total weight of the resin combination. In some embodiments, the catalyst content in the resin combination is preferably 0.5 phr to 1.2 phr. In some embodiments, the catalyst is a catalyst called DCP provided by ARKEMA.
[0038] The resin composition of the present invention can be suitable for forming a substrate for an electronic component. In some embodiments, the substrate is a copper foil substrate. In some embodiments, the substrate has the following specifications: a dielectric constant (Dk) of less than or equal to about 3.5; a dielectric loss (Df) of less than or equal to about 0.003; a glass transition temperature (Tg) greater than 260°C (e.g., about 260°C to 270°C); a peel strength greater than or equal to about 5 lb / in (e.g., about 5 lb / in to 6.5 lb / in); and / or heat resistance passes the test.
[0039] The following is a detailed description of the implementation and efficacy of the present invention using the copper foil substrates made of the resin compositions of the Examples and Comparative Examples. However, the present invention is not limited to the following Examples and Comparative Examples.
[0040] According to the component ratio in Table 1 below, the resin composition is mixed with butanone to form a varnish of a thermosetting resin composition. The obtained varnish is impregnated with Nan Ya fiberglass cloth (Nan Ya Plastics Co., Ltd., cloth type 1078LD) at room temperature, and then dried for several minutes at about 130°C (impregnation machine temperature) to obtain a prepreg with a resin content of 60% by weight. Then, 4 prepregs are stacked layer by layer between two copper foils of about 35μm thickness, and the temperature is kept constant for 20 minutes at a pressure of 25kg / cm2 and a temperature of 85°C, and then heated to 210°C at a heating rate of 3°C / min, and then kept constant for 120 minutes, and then slowly cooled to 130°C to obtain a 0.5mm thick copper foil substrate.
[0041] In Examples 1 to 6, the "DCPD-BMI" used is a bismaleimide resin (DCPD-MI) having a structure represented by the aforementioned formula (2).
[0042] In Examples 2 to 4, the "KI-50P" and "KI-70" used are bismaleimide resins sold by KI Chemical Industry Co., LTD., Japan under the trade names of KI-50P and KI-70 series, respectively.
[0043] In Example 1, Example 5, Example 6, Comparative Example 2, Comparative Example 3 and Comparative Example 6, the "MIR-3000" and "MIR-5000" used are bismaleimide resins sold by Nippon Kayaku Co., Ltd. under the trade names of MIR-3000 and MIR-5000 series, respectively.
[0044] In Comparative Examples 1 to 6, the "BMI-1000" and "BMI-2300" used are bismaleimide resins sold by DAIWA FINE CHEMICALS (TAIWAN) CO., LTD. under the trade names of BMI-1000 and BMI-2300 series, respectively.
[0045] In Examples 1 to 6 and Comparative Examples 1 to 6, the “HPC-8000” used is a hardener sold by DIC (Dainippon Ink & Chemicals, Inc.) under the trade name of HPC-8000 series.
[0046] In Examples 1 to 6 and Comparative Examples 1 to 6, the “DCP” used is a catalyst sold by ARKEMA under the trade name of DCP series.
[0047] In Examples 1 to 6 and Comparative Examples 1 to 6, the “Z-6030” used is a siloxane coupling agent sold by Dow Chemical Company under the trade name of Z-6030 series.
[0048] In Examples 1 to 6, the "437" used is an epoxy resin sold by Nanya Plastics Co., Ltd. under the trade name of 437 series.
[0049] In Comparative Examples 1 to 3, the "NC-3000-H" used is an epoxy resin sold by Nippon Kayaku Co., Ltd. under the trade name of NC-3000-H series.
[0050] In Comparative Examples 4 to 6, the “HP-9500” used is an epoxy resin sold by DIC (Dainippon Ink & Chemicals, Inc.) under the trade name of HP-9500 series.
[0051] In Examples 1 to 6, Comparative Examples 1, 2, 4 and 6, the "234" used is a benzoxazine resin sold by Nan Ya Plastics Co., Ltd. under the trade name of 234 series.
[0052] In Comparative Examples 3 and 5, the "BA-BXZ" used is a benzoxazine resin sold by Konishi Chemical Co., Ltd. under the trade name of BA-BXZ series.
[0053] In Examples 1 to 6 and Comparative Examples 1 to 6, the "PX200" used is a flame retardant sold by Dahachi Chemical Co., Ltd. under the trade name of PX200 series.
[0054] In Examples 1 to 6 and Comparative Examples 1 to 6, the SiO 2 used is a silica filler sold by Sibelco.
[0055] The glass transition temperature, dielectric constant, dielectric loss, peel strength and heat resistance of the copper foil substrate were evaluated in the following manner, and the evaluation results are listed in Table 1.
[0056] Glass transition temperature (Tg)
[0057] The glass transition temperature (Tg) of the resin composition in the copper foil substrate is measured by a dynamic mechanical analyzer (DMA). The higher the Tg, the better the ability of the resin composition to resist phase change, that is, the better the heat resistance.
[0058] Dielectric constant (Dk)
[0059] The dielectric constant at a frequency of about 10 GHz was measured using a dielectric analyzer (Model E4991A, manufactured by Agilent Technologies, Inc.) The smaller the dielectric constant, the better the dielectric properties of the resin composition in the copper foil substrate.
[0060] Dielectric loss (dissipation factor, Df)
[0061] The dielectric loss at a frequency of about 10 GHz was measured using a dielectric analyzer (Model E4991A, manufactured by Agilent Technologies). The smaller the dielectric loss, the better the dielectric properties of the resin composition in the copper foil substrate.
[0062] Peel strength
[0063] The peel strength between the prepreg and the copper foil was tested according to the IPC-TM-650-2.4.8 test method.
[0064] Heat resistance
[0065] The copper foil substrate sample is heated in a pressure cooker at 120℃ and 2atm for 120 minutes, then immersed in a soldering furnace at 288℃, and the time required for the board to burst is recorded. If the board burst time exceeds 10min, it is indicated as "OK", and if the board burst time is shorter than 10min, it is indicated as "NG".
[0066] [Table 1]
[0067]
[0068] <Evaluation Results>
[0069] As shown in Examples 1 to 6 of [Table 1], the copper foil substrate prepared by the resin composition having the composition ratio of the present invention has a measured Tg of not less than 260°C, a dielectric constant Dk of less than 3.5, and a dielectric loss Df of less than 0.003. Moreover, the copper foil substrates of Examples 1 to 6 also exhibit good peel strength (≥5 lb / in) and good heat resistance.
[0070] However, it can be seen from Comparative Examples 1 to 6 of [Table 1] that when the weight percentage of the bismaleimide resin is less than 30 weight % or greater than 50 weight %, the weight percentage of the epoxy resin is greater than 10 weight % and the weight percentage of the benzoxazine resin is greater than 10 weight %, the measured Tg is lower than 260° C., the dielectric constant Dk is greater than 3.5 and the dielectric loss Df is greater than 0.003.
[0071] In summary, the resin combination of the present invention has the characteristics of not generating polar groups when reacting, so it is not easily polarized in the electric field, thereby can significantly reduce its dielectric constant. In addition, the resin combination of the present invention can be directly or indirectly applied to copper foil substrates, and can be further processed to become other livelihood, industrial or suitable electronic components or electronic products (such as: circuit board or copper foil substrates). In addition, the resin combination of the present invention is helpful for the lifting of glass transition temperature, the lifting of peel strength, the lifting of heat resistance and / or the reduction of dielectric loss in the application of copper foil substrates.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A resin composition, characterized in that include: Based on the total weight of the resin composition, 30 to 50 wt % of a bismaleimide resin; 1 to 10 wt % epoxy resin; 1 to 10 wt% benzoxazine resin; 1 to 5 wt % of a hardener; 10 to 40 wt % of a filler; as well as 0.1 wt% to 3 wt% coupling agent.
2. The resin composition according to claim 1, characterized in that The bismaleimide resin includes DCPD-BMI, KI-50P, KI-70, MIR-3000, MIR-5000 or a combination thereof.
3. The resin composition according to claim 1, characterized in that The weight percentage of the epoxy resin is 1 wt % to 3 wt %.
4. The resin composition according to claim 1, characterized in that Also included is 0.1 wt % to 3 wt % of a catalyst.
5. The resin composition according to claim 4, characterized in that Also included is 5 to 15 weight percent of a flame retardant.
6. An electronic component, characterized in that: include: A substrate formed from the resin composition according to any one of claims 1 to 5.
7. The electronic component according to claim 6, characterized in that: The substrate has a dielectric constant less than or equal to 3.5 at a frequency of about 10 GHz.
8. The electronic component according to claim 6, characterized in that: The substrate has a dielectric loss of less than or equal to 0.003 at a frequency of about 10 GHz.
9. The electronic component according to claim 6, characterized in that: The glass transition temperature of the substrate is greater than or equal to 260°C.
10. The electronic component according to claim 6, characterized in that The substrate is a copper foil substrate.